PERSEPSI GURU TERHADAP BAHAN AJAR BAHASA MAKASSAR BERBASIS MULTIMEDIA DI SMA/SMK/MA/SLALB DI SULAWESI SELATAN - Kembong Daeng; Sakinah Fitri (SEMINAR NASIONAL DIES NATALIS 62, 2023)
This study aims to determine teachers' perceptions of multimedia-based Makassar language and literature teaching materials so that the results can serve as guidelines in producing multimedia-based Makassar language and literature teaching materials for SMA/SMK/MA/SMALB students in South Sulawesi. The type and form of research carried out refers to the Borg and Gall model which is modified from Sugiyono. This model includes 1) Potential and problems, 2) Data collection, 3) Product design, 4) Design validation, 5) Design revision, 6) Product trials, 7) Product revision. This series of research lasted for one year with the object of research being Makassar language teachers to find out the perceptions and criteria of multimedia-based teaching materials, including the development and testing of online-based Makassar language and literature teaching materials for SMA/SMK/MA/SMALB levels in South Sulawesi on the resulting teaching materials. The results obtained in this activity are: (1) online-based Makassar language teaching materials that are appropriate and in accordance with learning outcomes, and (2) the perceptions of SMA/SMK/MA/SMALB teachers in South Sulawesi towards the multimedia-based teaching materials that have been produced.